Case of Recurrent Takotsubo Cardiomyopathy - Choudhary, Abu B.; Raza, Adnan S.; Peterson, Stephen J.; Yadav, Rahul; Saleem, Shahzad; Haq, Salman (Cardiology and Cardiovascular Medicine, 2020)
Background: Takotsubo cardiomyopathy or stress induced cardiomyopathy is a transient regional systolic dysfunction of the left ventricle. It often mimics acute coronary syndrome (ACS) that is reversible and in the absence of angiographically obstructive coronary artery disease (CAD). Cases of recurrent takotsubo cardiomyopathy are not common. One study analyzed 749 patients with takotsubo cardiomyopathy from the multicenter registry, found that recurrence was about 4% and most recurrences occurred in the first 5 years. Case: 68 year old female with history of takotsubo cardiomyopathy presented to the hospital for abdominal pain, nausea, vomiting with symptoms starting after taking one of nitrofurantoin. On initial evaluation she was also endorsing worsening dyspnea and labs were concerning for elevated troponins. Echocardiogram revealed reduced ejection fraction and mid-apical walls akinesis. She underwent cardiac catherization which showed non-obstructive cardiomyopathy making recurrent takotsubo the likely diagnosis. Conclusions: Takotsubo cardiomyopathy is an acute transient reduction in systolic cardiac function that is induced by emotional or physical stressors. It is a nonobstructive cardiomyopathy that resolves after the initial stressor is resolved. Actual pathogenesis is still unclear however there are hypotheses it involves excessive catecholamine release. Recurrence is rare however it can occur and usually occurs in postmenopausal women with certain risk factors.